As vozes dos realismos nas narrativas de Milton Hatoum: romances, conto e audiovisual - Souza, Guilherme Alves de [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
This study addresses the complexity of a portion of Milton Hatoum's works and the audiovisual adaptations by Luiz Fernando Carvalho, Guilherme Cezar Coelho, and Sérgio Machado. It examines how the narrative configuration of these works reveals critical material about society, the subject, and its historical significance, highlighting the richness of narrative voices and the alternation between different categories, postures, and methods of literary realism. The analysis reveals that Hatoum's works exemplify the conjunction between literature and represented reality, offering an in-depth analysis of their social importance. For a realistic-critical and stylistic-sociological analysis, it was necessary to understand both categorically realistic conventions and the exploration of the reflection on the tradition of realism and its representations today. The comparison between the novels, the short story, and the audiovisual works demonstrates how the narrative voice highlights the tension between perspectives and the complexities of human relationships, significantly contributing to the understanding of contemporary Brazilian literature and its interpretations.

Este estudo aborda a complexidade de uma porção de obras de Milton Hatoum e as adaptações audiovisuais de Luiz Fernando Carvalho, Guilherme Cezar Coelho e Sérgio Machado. Examina-se como a configuração narrativa dessas obras revela material crítico sobre a sociedade, o sujeito e seu significado histórico, destacando-se a riqueza das vozes narrativas e a alternância entre diferentes categorias, posturas e métodos do realismo literário. A análise revela que as obras de Hatoum exemplificam a conjunção entre literatura e realidade representada, oferecendo uma análise profunda de sua importância social. Para uma análise realista-crítica e também estilística-sociológica foi necessário compreender desde as convenções categoricamente realistas à exploração da reflexão sobre a tradição do realismo e as suas representações nos dias de hoje. A comparação entre os romances, o conto e as obras do audiovisual demonstra como a voz narrativa evidencia a tensão entre as perspectivas e as complexidades das relações humanas, contribuindo significativamente para o entendimento da literatura brasileira contemporânea e suas leituras.
The voices of realism in Milton Hatoum's narratives: Novels, short stories and audiovisual
Keywords: Hatoum, Milton 1952; Literatura - Adaptações; Ponto de vista (Literatura); Literatura e sociedade; Audiovisual; Narrative Voice; Comparative Literature; Society